Testimonies on Plato’s Unwritten Dialectic - Wesoły, Marian Andrzej (Peitho. Examina Antiqua, 2015)
The present account – conducted in the paradigm of the recent approach to Plato – comprises a new translation with a short introduction and source bibliography. It consists of three major parts: I. Plato’s own testimonies: arguments against writing; II. References within the dialogues to the dialectic of principles (a selection); III. Testimonia Platonica (a selection). Apart from the relevant parts of Plato’s dialogues, the testimonies of Aristotle, Theophrastus and Sextus Empiricus have been taken into account. The translation of the testimonies has been arranged in a more systematizing manner than it was in the previous editions. The idea is to provide the Polish reader with reliable sources on the widely discussed hermeneutics of the written and unwritten Plato.